Las miradas sobre el hombre - Bedoya Wilson, Ricardo (2007)
Film making, since its beginning on late 19th century, focused its attention in registry of human activities. It made of man and its manifestations a centre of interest and object of diverse representations. The manuscript reviews some of those human encounters along films and producers that showed man during its born, while loving and desiring, making decisions, building societies, feeling pain, dying along others.